Resilience bouncing back - Leigh, Richard; Video Education Australasia (Bendigo, Victoria : Video Education Australasia, 2005)
Best mates Ange and Tom the puppet explore what it means to be resilient. Based on the work of leading psychologist Emmy Werner, the program suggest people who are resilient have someone who cares for them, something to do and something to hope for
Title from title screen
Executive producer, Mark McAuliffe ; editor, Nick Hayward ; camera, Peter Zakharov, Richard Leigh
Narration: John Osborne
Keywords: Resilience (Personality trait); Conduct of life; Personality